Influence of process pressure on HW-CVD deposited a-Si : H films - Jadkar, Sandesh R.; Sali, J. V.; Kshirsagar, S. T.; Takwale, M. G. (Solar Energy Materials and Solar Cells, 2005)
Hydrogenated amorphous silicon (a-Si:H) films were deposited using pure silane (SiH4) without hydrogen dilution by hot wire chemical vapor deposition (HW-CVD) technique. The electrical, optical, and structural properties of these films are systematically studied as a function of process pressure (P-r). The device quality a-Si:H films with a photosensitivity > 10(5) were deposited at a deposition rate >40 Angstrom/s at low process pressure. However, a-Si:H films deposited at higher process pressures show degradation in their electrical and structural properties. The FTIR spectroscopic analysis showed that a-Si:H films deposited at low process pressure contain hydrogen mainly in mono-hydrogen (Si-H) configuration whereas films deposited at higher process pressure have hydrogen in di-hydrogen (Si-H-2) or poly hydrogen (SiH2)(n) complexes. The hydrogen content (C-H) in the films was found to be less than 4 at.% over the entire range of process pressure studied. This indicates that the growth of a-Si:H films is mainly from the atomic species (Si and H) evaporated from the hot filament and hydrogen gets incorporated in the film via gas-phase reactions and substrate gas interactions. The band gap, however was found similar to1.71 eV or much higher. We attribute high band gap at low hydrogen content may be due to presence of microvoids. Raman spectroscopic analysis showed increase in structural disorder and Rayleigh scattering with increase in the process pressure. (C) 2004 Elsevier B.V. All rights reserved.
2nd International Conference on Cat-CVD (Hot-Wire CVD) Process, DENVER, CO, SEP 10-14, 2002
Keywords: Electrical properties; FTIR spectroscopy; hot wire chemical vapor deposition; hydrogenated amorphous silicon; Raman spectroscopy

Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction

Polyethersulfone-expanded graphite nanocomposites: charge transport and impedance characteristics - Ramanujam, B. T. S.; Mahale, Rajashree Y.; Radhakrishnan, S. (Composites Science and Technology, 2010)
Polyethersulfone (PES)-expanded graphite nanocomposites have been prepared by solution blending route after sonicating expanded graphite in dichloromethane. It has been observed that ultrasonication results in nanosheets formation leading to a low percolation threshold of 3 wt.%. At 5 wt.% filler loading the conductivity is of the order of 10(-2) S/cm. Hopping type of charge transport occurs at 3.2 wt.% expanded graphite in PES below which capacitive effects couple. The effective dielectric constant at low frequency increases with filler concentration. Impedance measurement has been carried out to evaluate interfacial capacitance which, for 3.2 wt.% expanded graphite addition in PES, increases to 110 pF from 32 pF for 1 wt.% expanded graphite in the polymer. DSC analysis shows an increment of 12 C in the T(g) of PES with 3 wt.% expanded graphite suggesting interaction between the polymer and filler. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Electrical properties; Modeling; Polymers; Scanning/transmission electron microscopy (STEM)

Influence of Mg2+ substitution on the magnetic and electrical properties of Li-Zn ferrite thick films synthesized with PVA matrix - Rendale, M. K.; Kulkarni, S. D.; Kulkarni, D. C.; Puri, Vijaya (Microelectronics International, 2011)
Purpose - The purpose of this paper is to investigate the effect of Mg2+ substitution on the magnetic and electrical properties of Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 thick films synthesized with polyvinyl alcohol (PVA) matrix. Design/methodology/approach - The nanoferrites Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) were synthesized by chemical technique using aqueous solution of PVA (the matrix) and thick films were fabricated by screen printing technique. The DC magnetic hysteresis measurements, AC magnetic susceptibility and DC electrical resistivity were measured as a function of temperature. Findings - The lattice parameter of thick film Li0.35-x Mg-2x Zn-0.3 Fe2.35-xO4 (x = 0, 0.07, 0.14, 0.21, 0.28 and 0.35) increases with the substitution of Mg2+ ions for Li1+ and Fe3+. The surface morphology of the thick films showed the grain size increasing with Mg2+ substitution till x = 0.21 and then decreasing for the higher concentrations of magnesium. The magnetic moment n(B) (mu(B)) computed from the M-s obtained by extrapolation of the magnetization curve showed a gradual decrease with the composition till x = 0.21, beyond which a sudden decrease was observed. The resistivity of the films at room temperature had variation with composition x, similar to that of magnetic moment. The activation energies Delta E-F and Delta E-P were found to vary with composition x of the ferrite system. Originality/value - The paper reports, for the first time, the magnetic and electrical properties of fritless Li0.35-xMg2xZn0.3Fe2.35-xO4 thick films using PVA polymer matrix. Up to x = 0.21 (Mg2+), grain size increases and Curie temperature decreases beyond which reverse effect takes place.
Keywords: Alternating current; Direct current; Electrical properties; Films (states of matter); Magnetic moments

Poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite based thin films for Schottky diode application - Gupta, Bhavana; Mehta, Minisha; Melvin, Ambrose A.; Kamalakannan, R.; Dash, Sitaram; Kamruddin, M.; Tyagi, A. K. (Materials Chemistry and Physics, 2014)
Transparent, conductive films of poly (3,4-ethylenedioxythiophene) (PEDOT) and poly (3,4-ethylenedioxythiophene)-few walled carbon nanotube (PEDOT-FWCNT) nanocomposite were synthesized by in-situ oxidative polymerization and investigated for their Schottky diode property. The prepared films were characterized by UV-Vis spectroscopy, thermal gravimetric analysis (TGA), surface resistivity, cyclic voltametery, scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM). SEM reveals the formation of homogeneous and adhesive polymer films while HRTEM confirms the uniform wrapping of polymer chains around the nanotube walls for PEDOT-FWCNT film. Improved thermal stability, conductivity and charge storage property of PEDOT in the presence of FWCNT is observed. Among different compositions, 5 wt. % of FWCNT is found to be optimum with sheet resistance and transmittance of 500 Omega sq(-1) and 77%, respectively. Moreover, the electronic and junction properties of polymer films were studied and compared by fabricating sandwich type devices with a configuration of Al/PEDOT or PEDOT-FWCNT nanocomposite/indium tin oxide (ITO) coated glass. The measured current density-voltage characteristics show typical rectifying behavior for both configurations. However, enhanced rectification ratio and higher forward current density is observed in case of PEDOT-FWCNT based Schottky diode. Furthermore, reliability test depicts smaller hysteresis effect and better performance of PEDOT-FWCNT based diodes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Composite materials; Electrical properties; Polymer; Thin films

Polypropylene-based conducting nanocomposites: effect of aspect ratio of second conducting filler on the electrical percolation - Ramanujam, B. T. S.; Radhakrishnan, S.; Deshpande, S. D. (Journal of Thermoplastic Composite Materials, 2017)
Powder-mixed polypropylene (PP)-graphite binary composites exhibit an electrical percolation threshold at 10 wt% graphite signifying insulator-semiconductor transition. Three conducting fillers such as carbon black (CB), sonicated expanded graphite (s-ExGr), and carbon nanofiber (CNF) are mixed with PP-7 wt% graphite binary composites. The electrical percolation threshold has been found to have inverse relation to the aspect ratio of second conducting fillers in hybrid composites. The aspect ratio of second conducting fillers varies in the order CB < ExGr < CNF. The electrical percolation threshold is found to vary for the hybrid composites as 2.2 wt% for CB addition, 0.75 wt% for ExGr addition, and 0.2 wt% for CNF addition in the PP-7 wt% graphite binary composites. When the aspect ratio of second conducting fillers increases, they reduce the barrier for the charge transport. The second conducting fillers occupy the interspace of graphite and alternating current studies show that the effective dielectric constant increases with the concentration of second conducting filler in the hybrid composites. The composites are characterized by transmission electron microscopy and scanning electron microscopy. Melt-crystallized PP-7 wt% graphite-CNF composites exhibit higher percolation threshold due to decrease in the polymer viscosity which increases the interparticulate distance.
Keywords: carbon nanofiber; Conducting polymer composites; Electrical properties; graphite nanosheets; hybrid composites; percolation; scanning; transmission electron microscopy